Assessment of Public Relations’ Practice of Edo State University Uzairue, Edo State, Nigeria - Obinna Johnkennedy Chukwu; Ewomazina Daniel Akpor; Olley Oritesesan Wilfred (Randwick International of Education and Linguistics Science Journal, 2021)
The study was carried out to assess public relations’ practice of Edo State University Uzairue. The study was predicated on Systems Theory (ST). The objectives were to determine the extent whether or not the Institution has a functional public relations department and to evaluate the extent of its public relations activities’ effectiveness, amongst others. Interview schedule was used to elicit information from the public relations office headed by the public relations officer. Findings indicates, amongst others, that the University has a public relations office, but does not have public relations department, and that the extent of her public relations activities’ effectiveness is average, amongst others. Given the above and the enormity of the importance of public relations to the educational institutions, the study, thus, recommend that Edo State University Uzairue should set-up a PR department with its ancillary compliments; step-up, and also, utilise effective public relations strategies in order to achieve effectiveness in its public relations’ campaigns or activities.